Kedudukan Hukum Pengguna Jasa Pinjaman Online Selaku Korban Dikaitkan Dengan Undang - Undang ITE - Harahap, Nasruddin Khalil; Saleh, Idris; Wardana, Ahmad; H., Kurniawan; Munthe, Iqbal Pinayungan (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
AbstractThe existence of Online Loans (Fintech) often causes polemics due to the existence of an unreasonable forced collection system for customers, in the form of violence, threats, terror, defamation and slander. However, this is a cause and effect of customers failing to pay their debts, so regulations were made in the second amendment to the ITE Law which provides extra protection to customers. The aim of the research is to find out and analyze legal certainty regarding loans and the legal position of customers in relation to the ITE Law. The method used is normative juridical, using descriptive analysis, through literature and field studies, as well as data collection techniques, followed by data analysis. The results of the research are that Article 27B of the ITE Law limits the method of billing customers, if they violate it, the funder can be given criminal sanctions with the threat of imprisonment for a maximum of 6 (six) years. Looking at these provisions, the customer's position can be positioned as a victim of the online loan program. However, on the other hand, the author believes that customers cannot be said to be victims if the customer has defaulted because they did not pay off their debt. Due to this action, the fund provider has also suffered losses. This means that this article is not appropriate in placing customers as victims, because the rules regarding forced collection are already regulated in the Criminal Code and the ITE Law in other articles.